Self Control As Mediator Of Financial Literacy, E-Money, And Lifestyle Towards Consumptive Behavior In Students In Sintang - Dhafa Alvin Suhendra Abirama; Yasir Hudzaifah; Joko Susilo (UNIVED Press, 2025)
This research aims to examine the role of self-control as a mediator in the influence of financial literacy, e-money usage, and lifestyle on the consumptive behavior of students in Sintang. High consumptive behavior among students is often influenced by low financial literacy, increased e-money usage, and a consumptive lifestyle that has developed in the digital era. This research method uses a quantitative approach with data collection through questionnaires distributed to students in Sintang. and then analyzed using the Structural Equation Modeling (SEM) technique based on Partial Least Square (SmartPLS). The research results show that financial literacy has a positive and significant impact on students' consumptive behavior. Lifestyle has a positive and significant effect on self-control, but does not have a significant effect on consumptive behavior. Meanwhile, e-money does not have a significant effect on self-control. Additionally, self-control does not have a significant effect on the consumptive behavior of students. This study also found that there is no significant mediating effect of self-control between financial literacy, lifestyle, and e-money on consumptive behavior. These findings imply that efforts to control students' consumptive behavior require additional strategies beyond merely enhancing self-control.